TROPICAL URBAN FORESTS AS GREEN INFRASTRUCTURE FOR URBAN RESILIENCE - Sahrani Somadayo; Mariam Coulibaly; Tomo Zupan (Journal of Selvicoltura Asean, 2026)
As urban areas continue to expand, the challenges posed by climate change—such as flooding, heat islands, and pollution—demand innovative solutions for enhancing urban resilience. Tropical urban forests, as a form of green infrastructure, offer significant benefits in mitigating these issues while improving the quality of life for urban residents. This study explores the role of tropical urban forests in strengthening urban resilience, focusing on their ecological, social, and economic contributions. The research utilizes a mixed-methods approach, combining environmental data collection (air quality, temperature regulation, stormwater management) with surveys and interviews from urban planners, policymakers, and residents. Findings reveal that tropical urban forests help reduce air pollution by up to 12%, lower surrounding temperatures by 2.5°C, and absorb up to 30% of rainfall, significantly mitigating urban flooding. Socially, residents near urban forests reported improved mental health, increased physical activity, and stronger community bonds. This study concludes that tropical urban forests are vital in enhancing urban resilience by providing essential ecosystem services and promoting social well-being. Integrating these green spaces into urban planning policies is crucial for creating sustainable and resilient cities.